Facilitation of Transport and Trade in Sub-Saharan Africa : A Review of International Legal Instruments - Treaties, Conventions, Protocols, Decisions, Directives - de Matons, Jean Grosdidier (World Bank, Washington, DC, 2014)
Facilitating trade flows between countries belonging to the same sub-region does not only require adequate transport infrastructure, or the availability of competitive and reliable transport services. Both will be used effectively only to the extent allowed by the legal framework governing their operations. Similarly, better regional economic integration will be served not only through harmonization of national development policies, but also, and perhaps to a greater extent, through the preparation, ratification and implementation of supranational legal instruments, going from the subregion to the continent and to the level of international conventions. Those instruments provide the necessary framework underpinning the sustainable development of trade flows, themselves harbingers of economic growth and employment generation. Sub-Saharan Africa clearly illustrates this situation, where several sub-regions are working hard from East to West to establish institutional and economic ties to help stimulate the joint progress of forty-eight countries. Actually, as a result of both whimsical politics and geography, the existence in Africa of fifteen landlocked countries has only strengthened the need to codify the rules governing the exchanges between coastal states and landlocked ones, so that the latter can benefit from a facilitated access to external markets. So, while numerous efforts are at play to push ahead with the regional integration of the continent, it appeared timely to draw an inventory of the legal instruments in force in sub-Saharan Africa, aiming at facilitating transport and trade flows between countries of the region. This document presents this inventory, together with an analysis of the main components and characteristics of all listed instruments.